2015
DOI: 10.1039/c5gc00717h
|View full text |Cite
|
Sign up to set email alerts
|

Functional nano-dispensers (FNDs) for delivery of insecticides against phytopathogen vectors

Abstract: Sketch of cross-sectional view of particle containing uniform distribution of PLGA (not in scale) and imidacloprid for controlled release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Furthermore, the surface-functionalized silica nanoparticles can deliver DNA and drugs into animal cells and tissues [39] because nanoparticles drug carriers have the potential to cross physiological barriers and access different tissues [40]. These results concur with a report by Meyer et al [41], who found that the Functional Nano-Dispensers (FNDs) of imidacloprid was about a 200-fold reduction in the quantity of imidacloprid active ingredient needed to achieve similar mortality of Diaphorina citri as compared with the commercial formulation. Similar results were also reported by Saini et al [42]; they mentioned that the biological activity of pyridalyl nanocapsules was more efficient than the commercial product on H. armigera larvae and that increased toxicity of nanosized formulation on larvae maybe is because of increasing penetration of pyridalyl in the larval body.…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, the surface-functionalized silica nanoparticles can deliver DNA and drugs into animal cells and tissues [39] because nanoparticles drug carriers have the potential to cross physiological barriers and access different tissues [40]. These results concur with a report by Meyer et al [41], who found that the Functional Nano-Dispensers (FNDs) of imidacloprid was about a 200-fold reduction in the quantity of imidacloprid active ingredient needed to achieve similar mortality of Diaphorina citri as compared with the commercial formulation. Similar results were also reported by Saini et al [42]; they mentioned that the biological activity of pyridalyl nanocapsules was more efficient than the commercial product on H. armigera larvae and that increased toxicity of nanosized formulation on larvae maybe is because of increasing penetration of pyridalyl in the larval body.…”
Section: Resultssupporting
confidence: 81%
“…To become economically viable, a less expensive and more efficient deployment method for fir oil application must be developed. For instance, slow-release nano-dispenser technology that can be sprayed directly onto trees with conventional equipment has been proven to effectively increase the efficiency of insecticide release for management of D. citri in citrus with much lower (100 fold) rates of active ingredient needed [ 25 ]. Additionally, this tool may be more effective as part of a push-pull or stimulo-deterrent diversion strategy by using the repellent along with trap crop attractants [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the addition of PCL increases the hydrophilicity of PLA, thereby improving the diffusion ability of pesticides. [ 186 ] Therefore, such amphiphilic polymers can be used as a container to encapsulate pesticides in the polymeric matrix surrounded by a hydrophilic shell, which maximizes the exposed surface area of pesticides and greatly reduces the actual amount of pesticides used. Moreover, the encapsulated pesticides can also be lyophilized for storage.…”
Section: Nanopesticides For Plant Protectionmentioning
confidence: 99%